In vitro cytotoxicity of cadmium microparticles for rabbit pulmonary alveolar macrophages - Dubreuil, Alain; Bouley, Georges; Boudene, Claude (Scandinavian Journal of Work, Environment & Health, 1979)
A cytotoxic effect of cadmium monoxide microparticles on rabbit pulmonary alveolar macrophages was observed in vitro from 1 to 2 µg of metal cadmium per million cells (and per milliliter of incubation medium). This threshold was close to the one observed with lead microparticles, which in addition appeared to have a faster cytotoxic action. On the other hand, cadmium microparticles inhaled in vivo are known to be much more toxic to the respiratory system dnd much more slowly cleared from it than lead particles. These contradictions can be partially explained by our observation that in vitro the ability of alveolar macrophages to phagocytize microparticles was significantly lower for cadmium monoxide than for lead monoxide microparticles.
Keywords: alveolar macrophage; cadmium; cadmium microparticle; cytotoxicity; in vitro; microparticle; phagocytosis; pulmonary alveolar macrophage; rabbit pulmonary alveolar macrophage